Does Buying Intention Predict Buying Behavior? Research on Consumer Decision Making - Nadiya Windiyani; Muhammad Rizky Naufal Ariq Tuasyikal; Kurniawati Kurniawati (Dinasti Publisher, 2025)
Several variables are added and set in a series of theories of Purchase Behavior (TPB), carried out in this study. In general, the main variables in the TPB, namely Green Subjective Norms (GSN), Green Attitude (GA) and Green Perceived Control (GPBC) support the existence of Green Purchase Intention (GPI) and from this GPI in general will create Green Purchase Behavior (GPB), including those in previous studies. The addition of several variables that have a close relationship with GPB can change GPB from just theory to practice. The variables to be added are the moderation of Green Product Availability( GPA), the addition of variable Government Regulation (GR) and Price Sensitivity (PS). This article discusses research and surveys conducted with the application of TPB with the variables listed above on green products, namely environmentally friendly products, both in the form of food/beverages and simple household appliances that have a positive impact on environmental sustainability. With respondents as many as 222 people covering the classification of age groups and education and certain occupations, data processing was carried out with SEM-AMOS and gave the result that the results of testing seven hypotheses that test GSN, GA , GPBC and GPA ability to moderate the influence of GPI on GPB significantly affect GBP. This is consistent with previous research.